Study of MRI lesions in severe preeclampsia and eclampsia in General Government Hospital Guntur, India - P., Usha Devi; K., Swarupa Rani; Sravanthi, Triparna Satya; Sai Kirthi C. H., Bala Bhavana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Study of MRI lesions in patients with PE with severe features and eclampsia and its correlation with clinical findings and laboratory values. Methods: This prospective observational study was conducted in HDU, Department of Obstetrics and Gynecology, GGH Guntur. 50 patients with preeclampsia and eclampsia divided into two groups based on MRI findings: controls (normal MRI), cases (abnormal MRI). Results analyzed with Chi Square test and student T test. Results: Out of 50 cases, abnormal MRI findings were observed in 24 (48%) cases and 26 (52%) showed normal MRI findings. PRES lesions majority 20 cases (40%), GLIOSIS in 2 (4%) cases, CSVT in 1 (2%) patients, cerebral hemorrhage seen in 1 (2%) patient. Majority are unbooked cases n= 38 (76%), booked cases n=12 (24%). Symptoms like irritability, headache, unconsciousness, dimness of vision and seizures correlated well with positive MRI findings (P=0.001, P=0.001, P=0.002, P=0.005, P=0.000respectively). Nausea/vomiting and high BP recordings not correlated with positive MRI findings (P=0.21, P=0.312 respectively). Abnormality in blood counts, serum fibrinogen, serum uric acid, PT, APTT and PT INR are not correlated with positive MRI lesions. Conclusions: Symptoms/signs like unconsciousness, irritability, blurring of vision, headache, seizures, GCS <3 and unbooked status of patients of eclampsia and preeclampsia should be a warning for possible development of MRI brain lesions. Whereas nausea, vomiting and high BP recordings are not significantly associated with positive brain lesions in MRI.